Efeitos de dietas hiperglicídicas e hiperlipídicas sobre a peroxidação lipídica e a atividade da enzima deltaaminolevulinato desidratase em camundongos - Folmer, Vanderlei (2004)
Chronic intake of diets containing high proportion of glucose, sucrose or fat promotes the development of insulin resistance and type 2 Diabetes mellitus. Furthermore, high levels of glucose can produce permanent chemical alterations in proteins and lipid peroxidation. δ-Aminolevulinate dehydratase (δ-ALA-D), which is the second enzyme in the heme pathway, is a sulfhydryl-containing enzyme highly sensitive to the presence of pro-oxidants elements and has been found inhibited in diabetics. Thus, the present study was designed to evaluate the effects of hyperglycidic and hyperlipidic diets on the lipid peroxidation and δ-ALA-D activity in different tissues of mice. High-glucose consumption, during 25 weeks, caused a significant increase in plasma glucose and triglyceride levels, TBARS content in kidney and liver, and a decrease in hepatic δ-ALA-D activity in relation to high-starch diet-fed animals. Blood HbA1c level and TBARS concentrations (liver, kidney, and brain) were significantly higher in mice fed the high-fat diet compared with those fed the high-starch diet, after 16 weeks. δ-ALA-D activity (liver, kidney, and brain) of mice fed the high-fat diet was significantly lower than those of mice fed the high-starch diet. Furthermore, positive correlations were found between the HbA1c and TBARS levels and negative correlations were found between the HbA1c levels and δ-ALA-D activity in all the studied tissues. The effects of short-term high-sucrose consumption (4 weeks) on sub-acute cadmium treatment also were analyzed. There was a significant increase in TBARS levels (spleen and liver) in cadmium and high-sucrose plus cadmium-treated mice. Testicular δ-ALA-D activity of cadmium and sucrose plus cadmium-treated animals was significantly inhibited, whereas the enzyme activity increased in blood and spleen. Also, Na+/K+-ATPase activity was significantly decreased in brain and kidney of sucrose plus cadmium-treated animals. High-glucose or high-sucrose consumption, during 30 weeks, caused an important increase in body weight, abdominal fat index, and plasma glucose levels; and, a positive correlation was observed between the abdominal fat index and blood glucose levels. TBARS levels were significantly increased in brain and kidney of both high-glucose and high-sucrose fed mice. There was a significant inhibition of the δ- ALA-D activity in blood, brain, kidney, and spleen of both high-glucose and highsucrose- fed mice. The aged animals had reduced enzyme activity (kidney and spleen) and increased TBARS levels (kidney, liver) in relation to young mice. DTTreactivation of δ-ALA-D of high-glucose and high-sucrose groups was significantly elevated in relation to control, indicating a more oxidative status of this enzyme. This fact also was observed as control, high-glucose, and high-sucrose groups were compared to young mice. In general, the results of this study indicate that consumption of high-glucose, high-glucose, and high-fat diet promotes oxidative stress related to hyperglycemia, which in turn can stimulate glycation and oxidation of proteins leading to δ-ALA-D inhibition in mice. Furthermore, high-sucrose consumption and sub-acute cadmium treatment have interactive effects on cerebral and renal Na+/K+-ATPase, showing that a short-term intake of high quantity of sucrose can aggravate the toxicity of Cd2+. Importantly, δ-ALA-D activity alterations found in this work stated this enzyme as a potential target for screening the physiologic or pathologic protein glications and oxidations caused by both Diabetes mellitus and aging.